Anise Hyssop Agastache foeniculum Increases Lifespan, Stress Resistance, and Metabolism by Affecting Free Radical Processes in Drosophila - Strilbytska, Olha M.; Zayachkivska, Alina; Koliada, Alexander; Galeotti, Fabio; Volpi, Nicola; Storey, Kenneth B.; Vaiserman, Alexander; Lushchak, Oleh (Frontiers in Physiology, 2020)
Anise hyssop, Agastache foeniculum, is a widely used medicinal herb with known antioxidant properties. We studied how dietary supplementation with dried A. foeniculum leaf powder affected physiological and metabolic traits as well as activities of antioxidant enzymes and markers of oxidative stress in Drosophila melanogaster. Dietary hyssop extended the lifespan in a sex and genotype independent manner over a broad range of concentrations up to 30 mg/ml. Dietary supplementation with the herb significantly increased fecundity, resistance to oxidative stress and starvation. Higher transcript levels of Drosophila insulin-like peptide (dilp2) and decreased dilp3 and dilp6 transcripts together with increased levels of glycogen and triacylglycerols support an alteration of insulin signaling by the plant extract. Increased enzymatic activities of superoxide dismutase and aconitase as well as elevated protein and low molecular mass thiols also supported an alteration of free radical process in flies treated with dietary A. foeniculum leaf powder. Thus, physiological and metabolic traits as well as free radical processed may be affected by active compounds detected in extracts of anise hyssop leaves and contribute to the increased lifespan and reproductive (egg-laying) activity observed.